Using simulation modelling to examine the impact of venue lockout and last‐drink policies on drinking‐related harms and costs to licensees. (28th February 2017) - Scott, Nick; Livingston, Michael; Reporter, Iyanoosh; Dietze, Paul
Abstract: Objective: Many variations of venue lockout and last‐drink policies have been introduced in attempts to reduce drinking‐related harms. We estimate the public health gains and licensee costs of these policies using a computer simulated population of young adults engaging in heavy drinking. Method: Using an agent‐based model we implemented 1 am/2 am/3 am venue lockouts in conjunction with last drinks zero/one/two hours later, or at current closing times. Outcomes included: the number of incidents of verbal aggression in public drinking venues, private venues or on the street; and changed revenue to public venues. Results: The most effective policy in reducing verbal aggression among agents was 1 am lockouts with current closing times. All policies produced substantial reductions in street‐based incidents of verbal aggression among agents (33–81%) due to the smoothing of transport demand. Direct revenue losses were 1–9% for simulated licensees, with later lockout times and longer periods between lockout and last drinks producing smaller revenue losses. Conclusion: Simulation models are useful for exploring consequences of policy change. Our simulation suggests that additional hours between lockout and last drinks could reduce aggression by easing transport demand, while minimising revenue loss to venue owners. Implications for public health: Direct policies to reduce late‐night transport‐related disputes should be considered.